Implikasi Hukum Pembatalan Akta Pernyataan Para Pemegang Saham di Luar Rapat Umum Pemegang Saham: (Studi Putusan No. 46/Pdt.G/2023/PN Cbi) - Zieky Dhirga Satrio; Isdiyana Kusuma Ayu (Universitas Muhammadiyah Kotabumi, 2026)
This research examines the legal implications of the annulment of the Deed of Statement of Shareholders’ Resolutions Outside the General Meeting of Shareholders (GMS) drawn up by a notary, with a case study of the Cibinong District Court Decision Number 46/Pdt.G/2023/PN Cbi. The main issues addressed in this study include: the ratio decidendi of the panel of judges in Decision Number 46/Pdt.G/2023/PN Cbi concerning the annulment of the Deed of Statement of Shareholders’ Resolutions Outside the GMS; and the legal implications for the notary arising from the annulment of the Deed of Statement of Shareholders’ Resolutions Outside the GMS in the said decision. This research employs a normative legal research method using statutory and case approaches. Legal materials were obtained through library research and analysis of the Limited Liability Company Law, the Notary Office Law, and relevant court decisions. The study applies descriptive and prescriptive analysis to evaluate the legality of the deed’s preparation and the consequences of its annulment. The findings show that the annulment of the Deed of Statement of Shareholders’ Resolutions Outside the General Meeting of Shareholders (GMS) resulted from the failure to fulfill formal and substantive requirements of an authentic deed. The deed was not read before the appearers and did not reflect the shareholders’ true intention, thereby violating statutory provisions and the principle of authenticity. Consequently, the deed lost its evidentiary force and may result in administrative, civil, and potential criminal liability for the notary.